Effect of Cd1−xZnxS/ZnS core/shell quantum dot on the optical response and relaxation behaviour of ferroelectric liquid crystal. (24th July 2017) - Agrahari, Kaushlendra; Pathak, Govind; Katiyar, Rohit; Yadav, Geeta; Vimal, Tripti; Pandey, Shivani; Singh, Dharmendra Pratap; Gupta, Swadesh Kumar; Manohar, Rajiv
ABSTRACT: Dielectrics, polarizing optical microscopic and electro-optical measurements have been carried out on a core/shell quantum dot Cd1−x Znx S/ZnS dispersed ferroelectric liquid crystal (FLC). In the present study, quantum dots were dispersed into two different concentrations of 0.1 and 0.25 wt./wt.% in pure FLC. The electro-optical parameters of pure and QDs dispersed FLC were carried out as a function of applied voltage. A significant improvement in optical response time of QDs dispersed FLC system is one of the major finding of the present study which may be useful for fabrication of faster liquid crystal system.